The global prehistory of human migration - Bellwood, Peter S. (Wiley Blackwell, 2015)
Previously published as the first volume of The Encyclopedia of Global Human Migration, this work is devoted exclusively to prehistoric migration, covering all periods and places from the first hominin migrations out of Africa through the end of prehistory. Presents interdisciplinary coverage of this topic, including scholarship from the fields of archaeology, anthropology, genetics, biology, linguistics, and moreIncludes contributions from a diverse international team of authors, representing 17 countries and a variety of disciplinesDivided into two sections, covering the Pleistocene and Hol.